Expenditures on collective and individual services: Discussion on the classification of government expenditures with regard to their inclusion into growth models - Zuzana Machová (DANUBE: Law, Economics and Social Issues Review, 2014)
The aim of this paper is to examine the effects of government expenditures on long-run economic growth in developed countries using their different breakdown. Empirical analysis is performed for a panel of 34 OECD countries in the period 2000-2012. Above all, the results support the idea that conclusions of previous studies on this topic may be strongly distorted by inappropriate classification of expenditures, typically in the case of expenditures on education and health. These are usually considered productive and thus growth enhancing, but if their part of R&D expenditures is detached, their effect on growth is in fact negative. In general, it is concluded that government expenditures on individual services have negative effects on growth, while the impact of expenditures on collective services is positive.
Keywords: 330; Government Expenditures; Economic Growth; Collective Services; Individual Services